IMPROVING COMMUNITY AWARENESS IN NEW NORMAL APPLICATION THROUGH EXTENSIONS AT PHARMACEUTICAL WONOREJO SRAGEN - Rita Septiana (Universitas Tidar, 2021)
Until now, the Covid-19 pandemic was still a problem and limits various community activities such as work, study, and worship, as well as socializing / activities. The government's effort to keep moving various sectors, be it social, cultural, economic growth so as not to experience a slowdown, industry running and people not losing their income is by introducing new habits of life or what was called a new normal. With the enactment of the new normal, we begin to carry out activities outside the home while adhering to health protocols that have been regulated by the government, namely wearing masks when leaving the house, washing hands frequently with soap, and maintaining distance and avoiding crowds. The service activity entitled